Etika Konselor dalam Konseling Lintas Budaya - Rizky, Muhammad; Jamaris; Solvema (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
Counseling is the provision of services in the form of assistance provided by professional staff to a person or group of individuals with the aim of developing an effective daily life and handling problematic daily lives with an emphasis on independent individuals who are able to control themselves through the implementation of various types services and support activities in the learning process. Ethics is an action about what is considered good and what is considered bad and about moral rights and obligations, a set of principles or values relating to morals, values regarding right and wrong that are adhered to by a group or society. In the counseling process mistakes or biases often occur due to differences in cultural backgrounds between counselor and client which result in ineffectiveness in providing counseling services. We need to know that culture can be studied or seen through the way a person communicates, because culture is communication, while communication is part of culture.